Collection Fernand Graindorge. - Kunsthalle Basel; Bosmant, Jules, 1893-1975 (Basel : Kunsthalle Basel, 1954)
Archipenko, Alexander ; Arp, Hans (Jean) ; Bauchant, André ; Baumeister, Willi ; Bazaine, Jean ; Bissière, Roger ; Bonnard, Pierre ; Braque, Georges ; Cézanne, Paul ; Chagall, Marc ; Chauvin, Gabriel ; Dali, Salvador ; Degas, Edgar ; Delaunay, Robert ; Derain, André ; Dix, Otto ; Dufy, Raoul ; Ensor, James ; Ernst, Max ; Fresnaye, Roger de la ; Giacometti, Alberto ; van Gogh, Vincent ; Gris, Juan ; Hartung, Hans ; Hofer, Karl ; Jawlensky, Alexej von ; Kandinsky, Wassily ; Kirchner, Ernst Ludwig ; Klee, Paul ; Kokoschka, Oskar ; Lam, Wifredo ; Lardera, Berto ; Laurens, Henri ; Leger, Fernand ; Lipchitz, Jacques ; Magnelli, Alberto ; Manessier, Alfred ; Marcoussis, Louis ; Matisse, Henri ; Metzinger, Jean ; Miro, Joan ; Modigliani, Amedeo ; Monet, Claude ; Nolde, Ernst ; Permeke, Constant ; Picasso, Pablo ; Pignon, Edouard ; Redon, Odilon ; Rouault, Georges ; Rousseau, Henri ; Schneider, Gérard ; Severini, Gino ; Silva, Vieira da ; Singier, Gustave ; De Smet, Gustave ; Taeuber-Arp, Sophie ; Tanguy, Yves ; Ubac, Raoul ; Winter, Fritz
Frans
Collection Fernand Graindorge, Kunsthalle Basel, 28. August bis 3. Oktober 1954
boek